2013
DOI: 10.3892/ijmm.2013.1589
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan oligosaccharides downregulate the expression of E-selectin and ICAM-1 induced by LPS in endothelial cells by inhibiting MAP kinase signaling

Abstract: Abstract. The expression of adhesion molecules in endothelial cells elicited by lipopolysaccharide (LPS) is involved in the adhesive interaction between endothelial cells and monocytes in inflammation. In this study, in order to characterize the anti-inflammatory effects of chitosan oligosaccharides (COS) on LPS-induced inflammation and to elucidate the underlying mechanisms, the mRNA levels of E-selectin and intercellular adhesion molecule-1 (ICAM-1) were measured in porcine iliac artery endothelial cells (PI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 36 publications
2
8
0
Order By: Relevance
“…In this study, we showed that the protein level of ICAM-1 in the ICB was upregulated and that COS significantly decreased the ICAM-1 expression in a dose-dependent manner. Our findings are consistent with a previous report by Li et al, who demonstrated that COS downregulated the expression of ICAM-1 by inhibiting the activation of NF- κ B in LPS-treated porcine iliac artery endothelial cells [43]. …”
Section: Discussionsupporting
confidence: 94%
“…In this study, we showed that the protein level of ICAM-1 in the ICB was upregulated and that COS significantly decreased the ICAM-1 expression in a dose-dependent manner. Our findings are consistent with a previous report by Li et al, who demonstrated that COS downregulated the expression of ICAM-1 by inhibiting the activation of NF- κ B in LPS-treated porcine iliac artery endothelial cells [43]. …”
Section: Discussionsupporting
confidence: 94%
“…In this study, LCOS also inhibited the mRNA expression of NF-κB. Previous study has shown that COS suppressed the translocation of NF-κB p65 into the nucleus in a dosedependent manner (Li, Xu et al, 2014). In addition, COS inhibit NF-κB binding activity and the expression of RELA and IKBKB genes of NF-κB induced by TNF-α; moreover, COS show stimulatory effects on AP-1-binding activity and JUN gene of AP-1 pathway in Caco-2 cells (Bahar, O'Doherty, Maher, McMorrow, & Sweeney, 2012).…”
Section: Discussionsupporting
confidence: 66%
“…Adhesion molecules are involved in the adhesive interaction between endothelial cells and monocytes in inflammation. COS down regulate the expression of adhesion molecules E-selectin and ICAM-1 by inhibiting the phosphorylation of MAPKs and the activation of NF-κB in LPS-treated porcine iliac artery endothelial cells [ 70 ]. Sulfated chitosan inhibits P-selectin-mediated HL-60 leukocyte adhesion.…”
Section: Inflammationmentioning
confidence: 99%